Comparison of postoperative vascularization between collagen matrix duraplasty and conventional duraplasty after direct bypass surgery in Moyamoya disease: A single-institute retrospective cohort study - Izumi Yamaguchi; Yasuhisa Kanematsu; Kenji Shimada; Masaaki Korai; Takeshi Miyamoto; Shu Sogabe; Manabu Ishihara; Tatsuya Haboshi; Yasushi Takagi (World Neurosurgery: X)
Background: Moyamoya disease (MMD) is characterized by the development of collateral circulation through the dura mater and overexpression of vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (bFBGF). Type 1 collagen promotes VEGF- and bFBGF-dependent neovascularization. The usefulness of collagen matrix duraplasty has not been investigated in MMD, particularly regarding vascularization. The present retrospective study aimed to assess whether collagen matrix duraplasty enhances the postoperative vascularization in adult-onset MMD. Methods: Twenty-six patients (40 bypasses) who underwent direct bypass surgery for adult-onset MMD were included. The patients were categorized into a collagen matrix group (CMG; n = 17 [25 bypasses]) and a control group (CG; n = 9 [15 bypasses]). We compared postoperative vascularization with cerebral angiography, single-photon emission computed tomography (SPECT), and stroke-free survival. Results: The direct bypass was patent in 92 % of CMG and 86.7 % of CG, with no significant difference (p = 0.623). Middle meningeal artery blush was observed in 76 % of CMG and 80 % of CG, indicating similar development (p > 0.99). Matsushima angiographic grade was comparable between groups (good: CMG 20 %, CG 6.7 %; fair: CMG 72 %, CG 80 %; poor: CMG 8 %, CG 13.3 %), with no significant differences. The median relative cerebral blood flow significantly increased postoperatively in CMG (preoperative 0.85, postoperative 0.94; p = 0.009) but not in CG (preoperative 0.93, postoperative 0.94; p = 0.455). The two-year stroke-free survival based on duraplasty showed no significant difference (p = 0.726) between groups. Conclusions: Collagen matrix duraplasty does not enhance the postoperative vascularization status after direct bypass surgery in adult-onset MMD in the short term.